The Urgency of Heavy Equipment Tax Regulations Judging From Law Number 1 of 2022 - Hartoyo, H; Negara, Dharma Setiawan; ., Lufsiana (Journal of Ecohumanism, 2024)
The State, through the Government, both Central Government and Regional Government, has a function in providing services to the community (public service). Public services can take various forms, both physical and non-physical services. Through good public services, national and state life will become conducive and orderly. Besides that, public services require costs, one of which comes from taxes. Taxes are a reciprocal mechanism between the Government and the Community in the context of public services. One of the taxes discussed in this research is Heavy Equipment Tax (PAB). Initially, heavy equipment tax regulations were included in Law 28/2009 where heavy equipment was included in the motorized vehicle category. There is a Constitutional Court Decision Number 15/PUU-XV/2017 which cancels the phrase that heavy equipment is included in motorized vehicles and since then heavy equipment is no longer subject to heavy equipment tax, but Law 1/2022 has been issued which includes heavy equipment as a tax object. This research is normative legal research that uses a statutory approach and a conceptual approach.